Characterization of differentially expressed and lipid metabolism-related lncRNA-mRNA interaction networks during the growth of liver tissue through rabbit models - Wang, Guoze; Li, Maolin; Wang, Yi; Wang, Binbin; Pu, Hanxu; Mao, Jinxin; Zhang, Shuai; Zhou, Shi; Luo, Peng (Frontiers in Veterinary Science, 2022)
Background： Characterization the long noncoding RNAs (lncRNAs) and their regulated mRNAs involved in lipid metabolism during liver growth and development is of great value for discovering new genomic biomarkers and therapeutic targets for fatty liver and metabolic syndrome. Materials and Methods：Liver samples from sixteen rabbit models during the four growth stages (birth, weaning, sexual maturity, and somatic maturity) were used for RNA-seq and subsequent bioinformatics analyses. Differentially expressed (DE) lncRNAs and mRNAs were screened, and the cis/trans-regulation target mRNAs of DE lncRNAs were predicted. Then the function enrichment analyses of target mRNAs were performed through Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, respectively. The target protein interaction (PPI) and lncRNA-mRNA co-expression networks were constructed using string version 11.0 platform and R Stats. Finally, six lncRNAs and six mRNAs were verified taking RT-qPCR. Results：Liver Oil Red O detection found that the liver showed time-dependent accumulation of lipid droplets. 41,095 lncRNAs, 30,744 mRNAs, and amount to 3384 DE lncRNAs and 2980 DE mRNAs were identified from 16 cDNA sequencing libraries during the growth of liver. 689 out of all DE lncRNAs corresponded to 440 DE mRNAs by cis-regulation and all DE mRNAs could be regulated by DE lncRNAs by trans-regulation. GO enrichment analysis showed significant enrichment of 892 GO terms. Besides, 52 KEGG pathways were significantly enriched, including 11 pathways of lipid metabolism were found . After the low expression DE mRNAs and lncRNAs were excluded, we further obtained the 54 mRNAs were regulated by 249 lncRNAs. 351 interaction pairs were produced among 38 mRNAs and 215 lncRNAs through the co-expression analysis. The PPI network analysis found that 10 mRNAs such as 3β-Hydroxysteroid-Δ24 Reductase (DHCR24), lathosterol 5-desaturase (SC5D), and acetyl-CoA synthetase 2 (ACSS2) were highly interconnected hub protein-coding genes. Except for MSTRG.43041.1, the expression levels of the 11 genes by RT-qPCR were the similar trends to the RNA-seq results. Conclusion：The study revealed lncRNA-mRNA interation networks that regulate lipid metabolism during liver growth, providing potential research targets for the prophylaxis and treatment of related diseases caused by liver lipid metabolism disorders.